The investigation of kinetics dissolution of prolonged indapamide drugs in biorelevant media - E. Yu. Sannikova; A. A. Kruglyakova; I. E. Shokhin; G. V. Ramenskaya (Сеченовский вестник)
In the current work there was performed the development of the method of determination dissolution kinetics in biorelevant media of slightly soluble substance, for example indapamide. The method was validated in terms of specificity, linearity, precision, accuracy, analytical range. The method was applied to dissolution kinetic studies of extended-release indapamide preparations.